A preliminary investigation into discursive models of interpreting as a means of enhancing construct validity in interpreter certification - Clifford, Andrew (University of Ottawa (Canada), 2004)
Interpreter certification has been largely ignored by the literature in Interpreting Studies. What little research that does exist on the topic is understandably elementary, discussing concerns that are general in nature or describing the development of individual certification instruments. No research has as yet examined the psychometric properties of certification instruments, despite the urgings of legal precedent, the weight of professional opinion, and the requirements of professional standards. The present study has attempted to bridge this gap in two ways. First, to gain some sense of the current state of affairs in interpreter testing, a validation study of an existing certification test was conducted. Particular attention was paid to information about the test's constructs. Second, in a bid to improve construct validity, a new certification test was constructed and subsequently validated. Constructs in the new test were based on a discursive model of the interpreting process. Validation of the two tests revealed some interesting findings. Constructs in the existing test bore only a weak relationship to the interpreting profession. Also, the constructs did not prove to be useful in predicting relationships among the existing test scores. It was expected that three separate constructs would emerge from the data; instead, empirical evidence suggested that the data were unidimensional in nature. In contrast, constructs in the new test were strongly linked to the interpreting profession. They also proved to effectively predict relationships among the new test scores. It was expected that three separate constructs would emerge from the data, and empirical evidence suggested that this was, in fact, the case. The results of the present study indicate that there is room for improvement in the current state of interpreter testing, and that a test instrument based on discursive constructs is likely to demonstrate acceptable levels of validity. There is obviously a need for a great deal of future research on the psychometric aspects of interpreter certification, and it is strongly recommended that this research adopt a discursive approach.
Keywords: Education, Tests and Measurements.; Language, General.